The Effect of Pressure Gradient on Boundary Layer Receptivity - Johnson, Mark W.; Pinarbasi, Ali (SPRINGER, 2014)
This paper presents numerical results for the receptivity of three laminar boundary layers with zero (ZPG), adverse (APG) and favourable (FPG) pressure gradients. Each boundary layer is subjected to a series of simple freestream waveforms which can be considered as constituent parts of either an isotropic or a non-isotropic turbulent freestream. Each freestream waveform has a single frequency in each spatial direction and is divided into two mutually perpendicular components. The first component has a zero spanwise velocity and hence lies in the streamwise normal plane whereas the second component lies in a plane which is perpendicular both to this plane and the spatial frequency vector. High boundary layer receptivities are only obtained for a minority of these waveforms and so only the resulting flow structures for these waveforms are considered in detail. The dominant flow structures are identified as either Tollmien Schlichting (T-S) waves or streaky structures. The streaky structures can be induced by both freestream components, but the response to the second component, which results in streamwise vortices in the freestream, is considerably stronger and occurs over a much larger streamwise frequency range. The boundary layer is only receptive to a relatively narrow band of spanwise wavelengths ranging from approximately one to four times the local boundary layer thickness. The APG leads to receptivities which are more than double those for the FPG case. The ratio of the freestream fluctuation streamwise wavelength to the distance from the plate leading edge is identified as an important influential parameter for receptivity leading to streaks. Significant T-S activity is only observed for APG, but is also detected for ZPG.
Keywords: Boundary layer; Transition; Receptivity; FREE-STREAM TURBULENCE; NATURAL TRANSITION; MODE; DISTURBANCES; SIMULATIONS; GROWTH; Thermodynamics; Mechanics